Nomograph for Predicting Swelling Potential of Expansive Subgrade Soil (University of Khartoum Engineering Journal, 2022)
This paper investigates empirical correlation between expansive soil index properties and soil swelling. The paper uses the concept of Nomographs to develop one for prediction of soil swelling. Disturbed soil samples from different regions in Sudan were collected to represent the most challenging soils in the country. The samples were collected from Al-Qadarif (S1), Wad Medani (S2) and Al-Giraif East in Khartoum (S3). The basic properties of the soil samples were thoroughly measured. The three soils gave high swelling potential and high plasticity. The X-ray diffraction test results showed that S1 has the highest montmorillonite than the other two soils. Therefore S1 is considered as the most expansive soil compared with the other soils. The consistency factor which was developed can be used to correlate the basic properties of the soil with the soil swelling. The consistency factor is a combination of the moisture content, dry density, void ratio, liquid limit and plasticity index. These parameters are combined in a way reflecting the influence of each of them on the soil property. The swelling properties were measured for the soil samples compacted at different moisture content and different dry densities. Very good linear relationships were developed between the swelling properties and the consistency factor. The correlations developed were verified by using data reported by some previous researchers. Using the relationships developed in this study, Nomograph was designed so as to make easy to predict swelling potential.